Pesantren Transgender: Negosiasi Citra Tubuh di Pondok Pesantren Waria Senin-Kamis Notoyudan Yogyakarta: Transgender Islamic Boarding School: Body Image Negotiation at the Monday-Thursday Waria Islamic Boarding School in Notoyudan, Yogyakarta - Achmad Nur (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2012)
This study describes the intellectual and spiritual journey of transvestites organized by a boarding institution located in the village of Notoyudan, Yogyakarta. This boarding school was founded by Mother Mariyani with the aim of bridging and facilitating transvestites who wish to explore religious knowledge and worship quietly and reverently. From this objective reality, academic interests emerged, including: first, the use of the term